Security of Business Operations and Supervisory Functions of the State as Characteristics of the Business Environment - VYAKINA, Irina Vladimirovna (Journal of Advanced Research in Law and Economics, 2019)
Assessment of business community’s subjective perception of state control and supervision impact on the safety of the business environment as part of the ongoing reform of state control and supervisory activities. The study analyzes the results of surveys of small, medium and large enterprises’ managers in 2016-2018, including business entities of various types of economic activity and organizational and legal forms. The vast majority of respondents are small and medium businesses. At the end of 2016, 502 respondents were surveyed, at the end of 2017 – 287 business representatives, and 319 entrepreneurs took part in the survey in 2018. The surveys were initiated by the regional business ombudsman and the business community. A content analysis of the regulatory framework and economic and statistical evaluation of survey results were carried out; tabular and graphical data visualization methods were applied. Results: business representatives do not feel safe in the current business environment. In the subjective perception of entrepreneurs, there is no reduction in the administrative burden on business. At the same time, inspectors remain oriented on the collection of fines and the inspections remain fiscally targeted. There is an interdependence of the subjective perception of control and supervisory measures by business representatives and objective characteristics of the safety of the business environment, which have a significant impact on motivation and the objective results of the activities of economic entities.